Metabolic Enzyme Triosephosphate Isomerase 1 and Nicotinamide Phosphoribosyltransferase, Two Independent Inflammatory Indicators in Rheumatoid Arthritis: Evidences From Collagen-Induced Arthritis and Clinical Samples - Lei, Ming; Tao, Meng-Qing; Wu, Yi-Jin; Xu, Liang; Yang, Zhe; Li, Yan; Olatunji, Opeyemi Joshua; Wang, Xiao-Wan; Zuo, Jian (Frontiers in Immunology, 2022)
Metabolic intervention is a novel anti-rheumatic approach. The glycolytic regulator NAMPT has been identified as a therapeutic target of rheumatoid arthritis (RA), while other metabolic regulators coordinating NAMPT to perpetuate inflammation are yet to be investigated. We continuously monitored and validated expression changes of Nampt and inflammatory indicators in peripheral while blood cells from rats with collagen-induced arthritis (CIA). Gene transcriptional profiles of Nampt+ and Nampt++ samples from identical CIA rats were compared by RNA-sequencing. Observed gene expression changes were validated in another batch of CIA rats, and typical metabolic regulators with persistent changes during inflammatory courses were further investigated in human subjects. According to expression differences of identified genes, RA patients were assigned into different subsets. Clinical manifestation and cytokine profiles among them were compared afterwards. Nampt overexpression typically occurred in CIA rats during early stages, when iNos and Il-1β started to be up-regulated. Among differentially expressed genes between Nampt+ and Nampt++ CIA rat samples, changes of Tpi1, the only glycolytic enzyme identified were sustained in the aftermath of acute inflammation. Similar to NAMPT, TPI1 expression in RA patients was higher than general population, which was synchronized with increase in RFn as well as inflammatory monocytes-related cytokines like Eotaxin. Meanwhile, RANTES levels were relatively low when NAMPT and TPI1 were overexpressed. Reciprocal interactions between TPI1 and HIF-1α were observed. HIF-1α promoted TPI1 expression, while TPI1 co-localized with HIF-1α in nucleus of inflammatory monocytes. In short, although NAMPT and TPI1 dominate different stages of CIA, they similarly provoke monocyte-mediated inflammation.